Acidic pH‐Responsive siRNA Conjugate for Reversible Carrier Stability and Accelerated Endosomal Escape with Reduced IFNα‐Associated Immune Response1. Issue 24 (29th April 2013) - Takemoto, Hiroyasu; Miyata, Kanjiro; Hattori, Shota; Ishii, Takehiko; Suma, Tomoya; Uchida, Satoshi; Nishiyama, Nobuhiro; Kataoka, Kazunori
<x xml:space="preserve">Abstract</x> An siRNA conjugate is based on an acid‐labile maleic acid amide linkage for programmed transfer of siRNA from the endosome to the cytosol and siRNA release in the cell interior. The procedure relies on reversible stability in response to endosomal acidic pH value. The complexed polyionic conjugate achieved gene silencing in cultured cancerous cells with negligible side effects.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>